Integrating Folklore in Modern Education: A Review of Interactive Materials and SDGs Alignment - Nuraini, Hery; Gailea, Nurhaedah; Samanhudi, Udi (FKIP Universitas Lampung, 2025)
Integrating Folklore in Modern Education: A Review of Interactive Materials and SDGs Alignment. Objectives: Integrating local culture through folklore is increasingly used to support next-generation learning competencies, here defined as learning performance, language/communication, cultural literacy, creativity, collaboration, critical thinking, ecoliteracy, and basic digital skills, while advancing SDG 4 (Quality Education), especially Target 4.7 on education for sustainable development and cultural diversity. Methods: The research employed a Systematic Literature Review (SLR) across Scopus, WoS, SINTA, ERIC, and Index Copernicus, using predefined inclusion criteria and quality appraisal. Findings: Across 35 studies, folklore-embedded interactive materials most consistently aligned with gains in learning performance and language/communication, with frequent co-benefits in cultural literacy and critical thinking when tasks were scaffolded through inquiry, story-based reflection, and locally meaningful problems. Evidence clusters were concentrated in Indonesia, which we interpret as a contextual pattern examined in the full paper and possibly reflecting glocalization in educational research ecosystems and/or national research policy incentives rather than a universal dominance. Conclusion: Taken together, the reviewed evidence supports a cautious, convergent claim: folklore-based interactive materials are associated with improvements in core competencies linked to SDG 4.1 (effective learning outcomes) and SDG 4.7 (cultural diversity and sustainable values), particularly when paired with teacher scaffolding and authentic tasks. The review contributes a mechanism-oriented synthesis: a “Folklore-as-Context” pathway (cultural familiarity → relevance → engagement → higher-order thinking) that specifies how and under what classroom conditions folklore supports 21st-century competencies, extending prior work that treated “local wisdom” and “innovation” only at a general level. Keywords: folklore, interactive learning materials, learning skills, systematic literature review.